The Effect of Price, Product Quality, Service Quality on Consumer Purchase Decisions at Solaria Cafe and Restaurant, Sorong City - Landjang, Xenia Irene Sandy; Edwar, Rizka Cintya; Mangopo, Yuni Riskita; Damanik, Lisa Gresti Sella (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2024)
Business competition in this era of globalization seems increasingly tight along with the increasing business competition, consumers or buyers are increasingly careful in choosing products in terms of purchasing decisions. This study aims to analyze the effect of price, product quality and service quality on consumer purchasing decisions at the Solaria Café and Resto, Sorong City. The method used in this study is the quantitative method. The number of samples used was 190 consumers of the Solaria Café and Resto, Sorong City. Then the data collection technique by distributing and distributing questionnaires to predetermined samples. Furthermore, the data is processed using the SPSS analysis technique. The results of this study indicate that (1) Price has a positive and significant influence on consumer purchasing decisions (2) Product quality has a positive and significant influence on consumer purchasing decisions (3) Service quality has a positive influence on consumer purchasing decisions, this influence is not significant. So it is concluded that hypotheses 1 and 2 in this study are accepted while hypothesis 3 is not accepted.